Fryda Solomonivna Leontyeva - "ORTHOPAEDICS, TRAUMATOLOGY AND PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The article is devoted to the well-known specialist in the field of clinical laboratory diagnostics, biochemist, teacher and organizer, candidate of biological sciences, senior researcher, head of the department of laboratory diagnostics and immunology F. S. Leontieva.